Community Outreach on Dengue Fever Prevention and the Use of Ovitraps: A Collaborative Initiative Between the Faculty of Health Sciences, Malahayati University, and Universiti Putra Malaysia - Agung Aji Perdana; Dina Dwi Nuryani; Lolita Sary; Nova Muhani; Wayan Aryawati; Riyanti Riyanti; Agustina Retnaningsih; Diah Astika Winahyu; Annisa Mayang Soliha; Syafik Arisandi; Maharani Kartini; Muhammad Putra Pratama (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2026)
Dengue Hemorrhagic Fever (DHF) remains a significant public health problem in tropical regions, including Indonesia and Malaysia. Population mobility, environmental changes, and limited community participation in vector control contribute to the persistence of dengue transmission. This community service activity was conducted in Hajimena Village, South Lampung Regency, on October 30, 2025, as a promotive and preventive effort in community-based dengue prevention. The program aimed to improve community understanding and awareness of dengue prevention through integrated health education and the utilization of ovitraps as a simple and environmentally friendly appropriate technology. The activity was implemented through collaboration between the Faculty of Health Sciences, Universitas Malahayati, and Universiti Putra Malaysia using a participatory education approach, interactive discussions, and hands-on practice in making and installing ovitraps. The evaluation was conducted using a qualitative descriptive approach through participatory observation, group discussions, and participant feedback. The results indicated an improvement in participants’ understanding of dengue, the life cycle of Aedes aegypti mosquitoes, and the importance of environmental-based vector control. Participants also demonstrated interest and readiness to independently apply ovitraps in their residential environments. This activity highlights that cross- institutional and cross-national collaboration can strengthen promotive and preventive efforts in community-based dengue control.